SUPPORTING EDUCATION IN MATH SCIENCES WITH A LOW-BUDGET LMS SAKAI - Petrova, Mimoza; Cabukovski, Vanco; Golubovski, Roman (Matematichki Bilten, 2016)
In this paper we present the Low-budget LMS Sakai, the analysis conducted and its selection from a list of few popular Low-budget LMSs, as well as its capability in presentation of math texts and formulas. The MATHEIS e-learning system for learning mathematics and informatics and its empowering with few software agent’s based features including the new developed GUPA (Graphic User Presentation Agent) software agent is emphasized. The plugins offered for Sakai allow powerful mathematics presentation capabilities, one of them being the WIRIS plugin. The paper is focused on the Sakai WIRIS plugin implementation.